2011
DOI: 10.1089/ars.2010.3508
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Studies of Antioxidant Pathway Genes and Schizophrenia

Abstract: The endogenous production of highly reactive oxidation species is an inherent by-product of cellular energy metabolism. Cellular antioxidant defense systems (AODS) comprising various antioxidants counter these damaging effects. Several lines of evidence, including postmortem studies, suggest increased oxidative stress in patients with schizophrenia. Some genetic association studies and gene-expression studies suggest that patients also may have altered ability to mount antioxidative mechanisms. As the genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 78 publications
(66 reference statements)
1
26
0
3
Order By: Relevance
“…Despite the inherent complexity of this area of research, with significant heterogeneity in results and negative studies, a constellation of key findings support an association between oxidative stress and the pathophysiology of schizophrenia. Genes involving antioxidant defenses are associated with increased risk of schizophrenia (2). Abnormal oxidative stress parameters have been reported in peripheral blood (3), red blood cells (RBCs) (4), neutrophils (5), platelets (6), cerebrospinal fluid (7), and postmortem brain (8) in patients with schizophrenia.…”
mentioning
confidence: 99%
“…Despite the inherent complexity of this area of research, with significant heterogeneity in results and negative studies, a constellation of key findings support an association between oxidative stress and the pathophysiology of schizophrenia. Genes involving antioxidant defenses are associated with increased risk of schizophrenia (2). Abnormal oxidative stress parameters have been reported in peripheral blood (3), red blood cells (RBCs) (4), neutrophils (5), platelets (6), cerebrospinal fluid (7), and postmortem brain (8) in patients with schizophrenia.…”
mentioning
confidence: 99%
“…Like other genetically complex disorders, linkage studies in schizophrenia have been relatively unsuccessful. Later studies investigated ''positional candidates,'' that is, genes localized to linked regions that are expressed in the brain and plausibly have a role in pathogenesis of schizophrenia, reviewed in this Forum by Chowdari et al (8), yielding several positional candidates: Dysbindin (DTNBP1), Neuregulin 1 (NRG1), D-amino-acid oxidase (DAO), and G72 (also named D-amino acid oxidase activator [DAOA]) (26).…”
mentioning
confidence: 99%
“…Genetic association studies have been conducted with polymorphisms in some of these genes, reviewed by Chowdari et al (8). They review GSH synthesis genes, GSH-related genes (GSTM1, GSTP1, GSTO1, GSTT1, and GSTT2), manganese SOD (MnSOD), and peptide methionine sulfoxide reductase (MSRA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Glutathione S-transferases (GSTs) are a family of prokaryotic and eukaryotic Phase II metabolic isozymes that provide critical defense against toxicants. 15,16 GSTs are expressed in many tissues in the human body. Previous studies have reported that GST levels of prefrontal cortex, peripheral blood, and cerebrospinal fluid were decreased in patients with SCZ, and suggested that GSTs play an important role in the development of SCZ.…”
Section: Introductionmentioning
confidence: 99%